Strategies for Human Tumor Virus Discoveries: From Microscopic Observation to Digital Transcriptome Subtraction - Mirvish, Ezra D.; Shuda, Masahiro (Frontiers in Microbiology, 2016)
Over 20% of human cancers worldwide are associated with infectious agents, including viruses, bacteria, and parasites. Various methods have been used to identify human tumor viruses, including electron microscopic observations of viral particles, immunologic screening, cDNA library screening, nucleic acid hybridization, consensus PCR, viral DNA array chip, and representational difference analysis (RDA). With the Human Genome Project, a large amount of genetic information from humans and other organisms has accumulated over the last decade. Utilizing the available genetic databases, Patrick S. Moore, Yuan Chang, and colleagues developed digital transcriptome subtraction (DTS), an in silico method to sequentially subtract human sequences from tissue or cellular transcriptome, and discovered Merkel cell polyomavirus (MCV) from Merkel cell carcinoma (MCC). Here we review the background and methods underlying the human tumor virus discoveries and explain how DTS was developed and used for the discovery of MCV.